SPATIAL DISTRIBUTION AND HABITAT PREFERENCE OF BIVALVIA IN THE COASTAL WATERS OF SIMPANG PESAK SUB DISTRICT, EAST BELITUNG DISTRICT - Irma Akhrianti; Dietriech G Bengen; Isdradjad Setyobudiandi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
The coastal waters of Simpang Pesak Sub-district, East Belitung Regency considered as a productive region and had a broad range of habitats for bivalvia. However, research on spatial distribution and habitat preference of bivalvia in this region is limited to none. The objectives of this research were to examine the effects of marine biophysical parameters and substrate quality on bivalvia. The research was started from Mei 2013 until June 2013 by using survey method and random systematic sampling approach. The results showed that there were 16 species of bivalves consisted of 14 genus from 7 family and dominated by Gafrarium pectinatum at station I (13.62 ind/m2, C=0.52, H’=0.6, muddy sandy), and station II (28.4 ind/m2, C=0.51, H’=1.04, sandy), Gafrarium tumidum at station III (59.9 ind/m2, C=0.51, H’=1.03, sandy), Scapharca pilula at Stasiun IV (61,6 ind/m2, C=0.5, H’=0.89, clay sandy). Spatial distribution and density of bivalves were influenced by particle size, C-organik, and other environmental factors such as current, dissolved oxygen, TSS, temperature, and salinity. Keywords: bivalves, distribution, habitat preference